(untitled) (Asian Journal of Medical and Biological Research, 2019)
The objectives of this study was to assess the prevalence of overweight and obesity in a sample of students from the Patuakhali Science and Technology University, Bangladesh and examine their usual eating habits. A cross-sectional survey of 260 students (65.38% male and 34.62% female) aged 20.81 ± 1.63 were chosen randomly from the Patuakhali Science and Technology University campus during May to July 2019. Students were asked to fill out a self-reported questionnaire that included questions on their eating, drinking and smoking habits. Also, their weight, height and body mass index were measured. Body mass index (BMI) was used to assess students’ weight status. Statistical analyses were performed using the SPSS software (version 23.0). Results shows that, majority of the students (67.3%) were of normal weight. Based on BMI classification, the prevalence of overweight was more common among the male students compared to females (23.5% vs. 10%). In contrast, prevalence of obesity was more common among female students (3.3% vs. 2.9%). A significant difference in BMI was observed between male and female students (p <0.01). The majority of the students (70.4%) reported that they took meals regularly. In terms of breakfast intake, less than half of the students (44.6%) reported that they took their breakfast daily. There was a significant gender difference in the frequency of snacks intake apart from regular meal (p <0.05). Female students were more prone to snacks consumption compared with male students. The unhealthy eating habits of the students was indicated by the fact that near about half of the students (46%) reported eating fried food daily or three to four times per week. Soft drinks consumption among the students were significantly associated with gender (p <0.05). The present results suggest the necessity of nutrition and health promotion programs for university students, especially programs emphasizing weight management. Asian J. Med. Biol. Res. June 2019, 5(3): 180-185